2017
DOI: 10.1111/pin.12611
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis is an excellent tool for quantifying Ki‐67 to predict the prognosis of gastrointestinal stromal tumor patients

Abstract: We investigated the quantification of Ki-67 staining using digital image analysis (IA) as a complementary prognostic factor to the modified National Institutes of Health (NIH) classification in patients with gastrointestinal stromal tumor (GIST). We examined 92 patients, focusing on the correlation between age, sex, primary tumor site, tumor size, predominant histologic type, mitotic index, modified NIH classification (low/intermediate vs high), Ki-67 quantitation, and recurrence-free survival (RFS). We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…And Sugita et al have found that 8% cutoff was a good supplementary prognostic factor for NIH risk stratification. Ki67 greater than 8% would indicate poor prognosis in both low -and intermediate-risk groups (14). Raut et al also concluded that Ki67 was one of the reference markers for imatinib's adjuvant treatment time after surgery (15).…”
Section: Discussionmentioning
confidence: 99%
“…And Sugita et al have found that 8% cutoff was a good supplementary prognostic factor for NIH risk stratification. Ki67 greater than 8% would indicate poor prognosis in both low -and intermediate-risk groups (14). Raut et al also concluded that Ki67 was one of the reference markers for imatinib's adjuvant treatment time after surgery (15).…”
Section: Discussionmentioning
confidence: 99%
“…The most newly published paper by Sugita et al applied a methodology similar to ours reaching an 8% score for whole slide scanning and Ki-67 labelling. The authors concluded that whole slide analysis raises the Ki-67 score in high-grade tumors to 8% and assume our study in hotspots could reach 10% or more [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, data are scarce regarding digital determinations of MIB-1 PIs in human meningiomas. However, similar studies have been performed in other tumors, such as breast cancer, 19 gliomas, 20 gastrointestinal stromal tumors, 21 and prostate cancer. 22 In those studies, a generally good correlation was established between manual and digital determinations of MIB-1 PIs, but the prognostic aspects varied.…”
Section: Introductionmentioning
confidence: 67%
“…22 In those studies, a generally good correlation was established between manual and digital determinations of MIB-1 PIs, but the prognostic aspects varied. [19][20][21][22] Accordingly, more studies are needed to establish reliable clinical data on MIB-1 PIs for various tumors.…”
Section: Introductionmentioning
confidence: 99%